Collocates of 'great' and 'good' in the Corpus of Contemporary American English and Indonesian EFL textbooks - Ikmi Nur Oktavianti; Japen Sarage (Studies in English Language and Education, 2021)
Previous studies have proven some discrepancies between language presented in EFL textbooks and the real use of English. This fact contradicts the teaching materials’ aim, which is intended to equip the learners to be communicatively competent. This study then investigates the use of adjectives, limited to ‘great’ and ‘good’ in terms of the frequent and strong co-occurrences, i.e., collocations, in a general reference corpus of Standard English to be compared with those in Indonesian EFL textbooks. The data were collected from both the corpus and the textbooks, but the analyses in the textbooks were generated based on the Mutual Information (MI) score of the collocates. Based on the comparison, it is evident that there are some similarities between adjective use in the textbooks and the corpus in terms of verb collocates of the adjectives. The mismatches, however, are quite remarkable, especially in terms of the variability of adverb collocates and the absence of prominent noun collocates in the textbooks. Pedagogically speaking, these results should be taken into consideration in writing the textbooks to enhance the quality of the language content prepared for the learners in the EFL context.